2020
DOI: 10.1093/biolinnean/blaa013
|View full text |Cite
|
Sign up to set email alerts
|

Bone histology yields insights into the biology of the extinct elephant birds (Aepyornithidae) from Madagascar

Abstract: Given that the biology of the recently extinct aepyornithids is poorly understood, we undertook a histological study of 29 skeletal elements of adult and juvenile specimens of Aepyornithidae, i.e. Aepyornis maximus, Aepyornis hildebrandti and Vorombe titan, in addition to a group of taxonomically unidentifiable juvenile Aepyornithiformes. Comparative analysis of the histology of the different skeletal elements showed that although the femur retained a good record of growth during early ontogeny, the tibiotarsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 57 publications
5
53
1
8
Order By: Relevance
“…Among all bones, the humerus was the most common bone developing SOs (77 in total), followed by the femur (11) and much less frequently the ulna (5) and tibia (3) (Table 3). This variation is not surprising since substantial skeletal heterogeneity has been previously reported in extant and extinct vertebrates, including differences in bone remodeling and microstructural properties among different skeletal elements (e.g., Amling et al, 1996; Bhat et al, 2019; Botha & Chinsamy, 2004; Cambra‐Moo et al, 2015; Chinsamy et al, 2020; Chinsamy & Warburton, 2020; Cullen et al, 2014; Goldstein, 1987; Martinez‐Maza et al, 2014; Nacarino‐Meneses et al, 2016; Padian et al, 2016; Parfitt, 2010; Peck & Stout, 2007; Ray & Chisanmy, 2004). However, considerable variation on methodological procedures, sampling methods, and taxonomic biases among these studies have greatly obscured the real nature of such patterns (see details in Cho & Stout, 2011; Padian et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Among all bones, the humerus was the most common bone developing SOs (77 in total), followed by the femur (11) and much less frequently the ulna (5) and tibia (3) (Table 3). This variation is not surprising since substantial skeletal heterogeneity has been previously reported in extant and extinct vertebrates, including differences in bone remodeling and microstructural properties among different skeletal elements (e.g., Amling et al, 1996; Bhat et al, 2019; Botha & Chinsamy, 2004; Cambra‐Moo et al, 2015; Chinsamy et al, 2020; Chinsamy & Warburton, 2020; Cullen et al, 2014; Goldstein, 1987; Martinez‐Maza et al, 2014; Nacarino‐Meneses et al, 2016; Padian et al, 2016; Parfitt, 2010; Peck & Stout, 2007; Ray & Chisanmy, 2004). However, considerable variation on methodological procedures, sampling methods, and taxonomic biases among these studies have greatly obscured the real nature of such patterns (see details in Cho & Stout, 2011; Padian et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Information documenting similar patterns in extant vertebrates is scarce and dispersed, for example, testudines (Bhat et al, 2019), equids (Nacarino‐Meneses et al, 2016), caprinids (Cambra‐Moo et al, 2015), and primates (Warshaw, 2008). Surprisingly, additional reports come from archeological and paleontological studies describing differences between bones in past human populations (Cho & Stout, 2011; Mulhern, 2000), as well as in a diverse range of extinct vertebrates such as non‐mammalian therapsids, equids, elephant birds, and dinosaurs (e.g., Chinsamy et al, 2020; Cullen et al, 2014; Martinez‐Maza et al, 2014; Padian et al, 2016). Despite the incidence of this phenomenon in a diverse group of vertebrates, there is a considerable gap in our understanding of the causes leading to differential skeletal homeostasis among these taxa.…”
Section: Introductionmentioning
confidence: 99%
“…2020; Chinsamy et al. 2020). Mammals with different lifestyles can be discriminated analyzing microstructural parameters such as bone compactness (e.g.…”
Section: Taxon Humeral N Femoral N Mean Humeral CC (%) Mean Femoral Cmentioning
confidence: 99%
“…Bone microanatomical studies of tetrapods have demonstrated that bone architecture (microanatomy) and internal tissue structure (histology) varies according to lifestyle adaptations ( Wall, 1983 ; Chinsamy, 1991 ; Ray, Chinsamy & Bandyopadhyay, 2005 ; Gray et al, 2007 ; Hayashi et al, 2013 ; Houssaye et al, 2016 ; Canoville, de Buffrénil & Laurin, 2016 ; Canoville & Chinsamy, 2017 ). Furthermore, bone histology of extant and extinct vertebrates provides direct assessment of life history and the biology of an animal ( de Ricqlès, 1969 , 1972 ; Francillon-Vieillot et al, 1990 ; Chinsamy, 1997 ; Horner, de Ricqlès & Padian, 1999 , 2000 ; Chinsamy-Turan, 2005 , 2012 ; Klein & Sander, 2008 ; Chinsamy et al, 2013 , 2019 , 2020 ; Woodward, Horner & Farlow, 2014 ; Woodward et al, 2015 ; Woodward et al, 2020 ; Huttenlocker & Botha-Brink, 2014 ; Botha-Brink, Soares & Martinelli, 2018 ; Cullen et al, 2020 ; Huttenlocker & Shelton, 2020 ; Botha, 2020 ). Several studies have examined the bone histology of the non-mammalian therapsids (see Chinsamy-Turan, 2012 and references therein), however, except for the early work of de Ricqlès (1972) , dinocephalians have been relatively under-studied.…”
Section: Introductionmentioning
confidence: 99%